Outcomes following resection of non‐small cell lung cancer in octogenarians. Issue 12 (2nd October 2018) - Vazirani, Jaideep; Moraes, Johanna; Barnett, Stephen; Johnson, Douglas F.; Knight, Simon; Miller, Alistair; Wright, Gavin; Alam, Naveed Z.; Conron, Matthew; Irving, Louis B.; Antippa, Phillip; Steinfort, Daniel P.
Abstract : Background: The treatment of choice for early stage non‐small cell lung cancer (NSCLC) is surgical resection. Little is known about the short‐ and long‐term outcomes among very elderly patients. We sought to determine predictors of short‐ and long‐term survival among octogenarians undergoing curative‐intent resection for NSCLC in Victoria, Australia. Methods: We retrospectively reviewed data from all patients aged ≥80 years who underwent curative‐intent resection for NSCLC over 12 years (January 2005–December 2016) across five tertiary centres. We examined effect of age, stage of disease, extent of surgery and lung function on short‐ and long‐term survival. Results: Two hundred patients aged ≥80 years underwent curative‐intent resections. Mortality at 30 and 120 days was 2.9% and 5.9%, respectively. Increased early mortality was observed among those ≥83 years, at 30 days (6.8% versus 0.8%, P = 0.044) and 120 days (12.2% versus 2.3%, P = 0.0096). Early mortality was highest among patients ≥83 years requiring lobectomy, compared to sub‐lobar resection at 120 days (17% versus 3.8%, P = 0.019). Long‐term survival was predicted by age and stage of disease. Among patients with Stage I disease aged <83 years, lobectomy was associated with superior 5‐year survival, compared to sub‐lobar resection (83% versus 61%, P = 0.02). Conclusion: In carefully selected elderly patients undergoing curative‐intent resection of early stage NSCLC, both short‐ and long‐term outcomes appear consistent with younger historical cohorts. Early mortality was associated with lobectomy in those with advanced age. Older patients undergoing lobectomy appeared to be at highest risk for early mortality, while younger patients with Stage I disease undergoing at least lobectomy appear to have the best long‐term survival.